2008
DOI: 10.1007/s11165-008-9079-8
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Actual Processes of Physicists’ Research and the Implications for Teaching Scientific Inquiry in School

Abstract: Investigation of scientists' actual processes of conducting research can provide us with more realistic aspects of scientific inquiry. This study was performed to identify three aspects of scientists' actual research: their motivations for scientific inquiry, the scientific inquiry skills they used, and the main types of results obtained from their research. To do this, we interviewed six prominent physicists about why and how they researched and what they obtained from their research results. We also analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
2
15
0
1
Order By: Relevance
“…Students cannot be expected to reinvent theoretical concepts entirely through inductive experimental activities; therefore, student experiments have to be accompanied by deductive, semideductive, or hypothesis-driven considerations. Moreover, most authentic inquiry in physics starts from a theory-driven or hypothesis-driven motive (Park, Jang & Kim, 2009). Third, teachers have to support students to move from schooloriented norms toward scientifically oriented norms.…”
Section: Results Of An Earlier Design Studymentioning
confidence: 99%
“…Students cannot be expected to reinvent theoretical concepts entirely through inductive experimental activities; therefore, student experiments have to be accompanied by deductive, semideductive, or hypothesis-driven considerations. Moreover, most authentic inquiry in physics starts from a theory-driven or hypothesis-driven motive (Park, Jang & Kim, 2009). Third, teachers have to support students to move from schooloriented norms toward scientifically oriented norms.…”
Section: Results Of An Earlier Design Studymentioning
confidence: 99%
“…Scientific inquiry is a way that scientists use for explaining the natural world and it is also the fundamental practice of science (Bybee, 2004). The teaching of scientific inquiry usually does not reflect authentic professionalism and thus distort the nature of science (Chinn & Mahotra, 2002;Park, Jang, & Kim, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Scientific inquiry skills include formulating and evaluating hypotheses, identifying and controlling variables, conducting experiments, interpreting and comparing results, and inferring conclusions (Ting & Phon-Amnuaisuk, 2010). Many educators have suggested that the process of inquiry is necessary to teach students to think scientifically (Park, Jang, & Kim, 2009;Windschitl, 2004). Windschitl (2004) claimed that the process of scientific inquiry is not a linear one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…따라서 상상력에 대한 관 점을 정의하고, 그에 따른 특성을 탐색하는 연구가 이 루어져야 한다. 과학자는 과학 연구를 통해 눈에 보이지 않는 것을 시각화하여 모형을 만들고, 결과로부터 새로운 현상 을 설명하며 (김영민, 2006;Park et al, 2009;West, 1991), 이 과정에서 상상력이 발휘된다. 과학 자의 상상력은 과학적 성취와 과학자의 사고과정을 포함한 과학 활동에서 중요한 역할을 수행한다는 점 에서 과학 교육 연구에서 중요하게 다루어져야 한다.…”
unclassified